Markers of endothelial activation and atherothrombosis in women with history of preeclampsia or gestational hypertension - Vickers, Mark; Ford, Isobel; Morrison, Rona; Prescott, Gordon; Watson, Stuart; Hannaford, Philip; Smith, Cairns; Campbell, Doris; Greaves, Michael (Thrombosis and Haemostasis, 2003)
Women who have had preeclampsia (PE) or gestational hypertension (GH) exhibit relatively high rates of circulatory diseases. PE is a disease associated with inflammation and vascular endothelial dysfunction. We therefore hypothesised that women with a history of PE or GH might have abnormal levels of markers of endothelial activation or inflammation, reflecting either an innate predisposition to preeclampsia or changes induced by the eclamptic process. Levels of von Willebrand factor, fibrinogen and C-reactive protein were compared in 392 women with a history of PE between 1951 and 1970, 297 women with a history of GH and 163 matched controls. Although no significant differences between those with either PE or GH and controls were noted, subjects with a history of PE had significantly higher CRP values than those with GH. No significant differences were found when the three groups were compared for von Willebrand factor or fibrinogen. Overall, the data do not support our hypothesis.In addition, our data document increasing von Willebrand factor levels increase with age, which may help explain the age dependent increase in venous or arterial thrombosis. Moderate alcohol consumption was also associated with lower levels of inflammatory markers.
Keywords: Preeclampsia; fibrinogen; von Willebrand factor; C-reactive protein; vascular endothelium